2012
DOI: 10.1007/s00464-012-2530-y
|View full text |Cite
|
Sign up to set email alerts
|

Single incision versus reduced port splenectomy—searching for the best alternative to conventional laparoscopic splenectomy

Abstract: RPAS is a good alternative to LS and SPAS. It improves the aesthetic results as compared to LS, whereas minimizes the technical challenges faced with SPAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…No patients were converted to OS in any group, but three patients required additional trocars to finish the SPAS. RPAS had an operative time comparable to that of LS and significantly shorter than the SPAS (16). The results of this unique study are insufficient to establish any evidence of superiority of RPAS and SPAS over LS, apart from the better postoperative comfort and cosmetic result.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…No patients were converted to OS in any group, but three patients required additional trocars to finish the SPAS. RPAS had an operative time comparable to that of LS and significantly shorter than the SPAS (16). The results of this unique study are insufficient to establish any evidence of superiority of RPAS and SPAS over LS, apart from the better postoperative comfort and cosmetic result.…”
Section: Resultsmentioning
confidence: 71%
“…Studies with shorter durations of follow-up had significantly higher relapse rates than studies with longer follow-up. It was concluded that splenectomy may have higher initial relapse rates in the first 2 years after surgery, (20) Splenic bed collection, peripancreatic fluid collections, 0% 6.25% 0% bleeding from the splenic artery stump, symptomatic PVT Nobili et al (17) Hemoperitoneum 0% 10% 0% Chen et al (9) Bleeding, pneumonia, subphrenic fluid collection, left pleural effusion 0% 11% 0% Wu et al (25) Subphrenic hematoma, bleeding 0% 0% 0% Zheng et al (27) Subphrenic abscess, bleeding 0.6% 8.4% 0% Zheng et al (26) N/A N/A N/A N/A Wu et al (24) Subphrenic hematoma, bleeding 0% 0% 0% Al-Mulhim (7) Acute chest syndrome, left subphrenic hematoma, left pleural effusion 0% 8.4% 0% Patel et al (18) PE, DVT, pneumonia, MI 0% 10% 0% Corcione et al (10) Fluid collections in the splenic fossa, subphrenic 0.3% 13% 1% abscesses, bleeding, intestinal ischemia Fraser et al (11) PVT, sepsis, bleeding, intestinal ischemia 3.9% 21.1% N/A Monclova et al (16) Bleeding from a vessel of the greater omentum, 0% 15.6% 3% subphrenic fluid collection, pancreatic fistula. Li et al (13) Wound complications, sepsis, subhepatic abscess, respiratory complications 0% 6.67% 0% Marte et al (14) Bleeding, OPSI 2.08% 8.8-35.7% 0% Wang et al (23) Bleeding, PVT 0% 6.9% 6.9% Vecchio et al (6) Conversion to open surgery was required in one patient because of 0% 0% 0% lack of anatomic definition of Calot triangle's structures.…”
Section: Critical Evaluationmentioning
confidence: 99%
“…After the literature search two prospective [122, 123] and four retrospective comparative studies [124127] have been selected for review, in which SIES splenectomy is compared to standard (or reduced port) laparoscopic splenectomy (LS). No randomized clinical trials have been published on this topic, which may be related to the fact that elective splenectomy is a rarely performed operation.…”
Section: Resultsmentioning
confidence: 99%
“…Key words: Cholecystectomy; laparoscopy; single-incision laparoscopic surgery (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%